The Integration of Cognitive Behavior Therapy with Passive Music Therapy to Improve Millennial Students' Self-Efficacy - Situmorang, Dominikus David Biondi; Mulawarman, Mulawarman; Wibowo, Mungin Eddy (Universitas Ahmad Dahlan, 2018)
The current study aimed to find out the effectiveness of group counseling with cognitive behavior therapy using passive music therapy in order to improve the millennial students' self-efficacy who were writing thesis. This study employed quantitative approach with quasi-experimental design. The subject of the study were seven millennial students of Guidance and Counseling Study Program (BK) of Atma Jaya Catholic University of Indonesia. Purposive sampling technique was employed to select the subject. The data were analyzed using one-way analysis of variance (ANOVA). The result of the study showed that group counseling with cognitive behavior therapy using passive music therapy was effective in improving millennial students' self-efficacy. The result of the study may contribute to the development of the field of guidance and counseling in developing an individual's self-efficacy through cognitive behavior therapy with passive music therapy.